The role of water user organizations in the sustainable use of groundwater in Peru - Villegas Vega, Paul (2020)
In this article, the author analyzes how water user organizations contribute to the sustainable use of groundwater in Peru. In order to do that, he begins by describing the regulatory instruments provided in the country for water resource management and the applicable regime for its use by water users, from which water users’ organizations are formed; after that, he presents the figure of these organizations as actors who contribute to the sustainability of groundwater and; finally, he makes a brief analysis of the sustainability of groundwater from the use by water users’ organizations.